Pendidikan Karakter Berbasis Nilai Islami di Madrasah Ibtidaiyah Negeri 1 Yogyakarta - Qoni'ah Musallamah; Wasith Achadi; Muqowim Muqowim (Lembaga Yasin AlSys, 2026)
Although character education has been widely studied, research that specifically examines its implementation based on madrasah culture at the state madrasah ibtidaiyah level remains limited. This study aimed to analyze the implementation of character education at Madrasah Ibtidaiyah Negeri (MIN) 1 Yogyakarta in shaping a generation of Literat Muda who are religious, of noble character, and socially caring. The research employed a descriptive qualitative approach with a case study design, with data collected through observation and in-depth interviews with the principal as the main informant, and analyzed interactively through the stages of data reduction, data display, and conclusion drawing. The findings show that character education at MIN 1 Yogyakarta is implemented in an integrated manner through classroom learning, habituation of religious practices, and programs rooted in the madrasah environment and culture. Character strengthening is carried out through teachers’ role modelling, the habituation of the 5S culture (senyum, sapa, salam, sopan, santun), and the integration of religious moderation values into learning activities and daily routines. These findings contribute to strengthening understanding of an integrative model of character education based on madrasah culture that is contextual and sustainable, and provide practical implications for the development of character education programs in other state madrasah ibtidaiyah.